Inklusi Sosial pada Bank Sampah Perpustakaan Rosella Genematrik dalam Menciptakan Ekonomi Baru pada Masyarakat Kelurahan Siantan Tengah Kecamatan Pontianak Utara - Kurniawan, Kurniawan (Literatify: Trends in Library Developments, 2024)
The purpose of this study is to the strategy of the Rosella Genematrik Library waste bank in creating a new economy in Siantan Tengah Village, North Pontianak, which is a social inclusion program that helps process waste sustainably with community participation. The library as a center for information sources has various functions in education, research, and recreation. Collaboration between waste banks and libraries can create an ecosystem that supports the growth of entrepreneurship in the fields of waste management and recycling. The research method used is qualitative with documentary study techniques and interviews. The researcher conducted research at the Rosella Genematrik Library waste bank in Siantan Tengah Village, North Pontianak District, West Kalimantan. This study discusses the strategy of waste banks as a social inclusion program to create a new economy in the community. Some of the proposed strategies include promotion on social media, development of community resources, providing facilities and services, campaigns to increase environmental awareness, incentive programs, sources of information, entrepreneurship training, environmental literacy, and development of environmentalist communities. In conclusion, waste banks can use this strategy to support a new economy that is more sustainable and a cleaner environment